OPTIMIZATION AND KINETICS STUDY OF BIOETHANOL PRODUCTION FROM PALM OIL MILL EFFLUENT UNDER ANAEROBIC PROCESS - Eng Diamant; Marisa Handajani (ITB Journal Publisher, LPPM ITB, 2016)
Abstrak: Various factors has influenced to the products during the anaerobic fermentation process pathway including pH as the main factors. This research study on kinetics of the bioethanol production at different pH conditions (5.5, 6.5-7.5 and 8.5) with artificial palm oil mill effluent with various concentrations of COD (10 g/L, 15 g/L, and 20 g/L) as a substrate. The optimum condition of pH value which provided the maximum bioethanol production under fermentation process from artificial wastewater will be re-implemented and adjusted the pH of palm oil mill effluent (POME) according to the characteristic of COD. Batch reactor will be used in this research study to preserve the microbial activity for converting substrate into bioethanol production within 72 hours. Nitrogen purged for the first 24 hours will be conducted to remove any residual oxygen from the reactor then internal gas in headspace of the reactor circulation system will be replaced as a mixing system. Microorganisms are taken from cow rumen mixed with palm oil mill effluent sludge. The kinetic studies will be determined such as product formation as bioethanol using Modified Gompertz model and substrate consumption using first-order kinetic. Bioethanol and acids yield and production rate will be determined as well. The result of ethanol production from the experiment was shown that the optimum pH condition from initial COD concentration of 10 g/L was in neutral condition and from 15 and 20 g/L were in acidic condition with the concentration of 12.36 g/L, 10.42 g/L, and 20.91 g/L, respectively. According to characteristic of POME wastewater, the concentration of COD was about 15 g/L then pH condition was operated into acidic condition (pH 5.5). From the experiment of the POME wastewater, the ethanol production obtained the maximum in 72 hours of 3.73 g/L. Ethanol yield and production rate from POME were 1.93 g/g and 51.87 mg/L/hr, respectively. Total volatile fatty acids yield and production rate from POME were 2.34 g/g and 62.95 mg/L/hr, respectively.secara rata-rata faktor keamanan sampah terkompaksi melewati standar TPA sementara dan permanen. Kata kunci: pH, kinetic, fermentation, ethanol production, palm oil mill effluent (POME) Abstract: Beberapa factor dapat mempengaruhi produk selama proses anaerobic fermentasi termasuk pH sebagai faktor utama. Penelitian ini mengkaji kinetika produksi bioetanol pada kondisi pH yang berbeda (5,5, 6,5-7,5 dan 8,5) menggunakan limbah pabrik kelapa sawit artifisial dengan berbagai konsentrasi COD (10 g/L, 15 g/L, dan 20 g/L) sebagai substrat. Kondisi optimum nilai pH yang menghasilkan produksi bioetanol maksimum dalam proses fermentasi dari limbah artifisial akan diimplementasikan kembali dan disesuaikan pH limbah pabrik kelapa sawit (POME) sesuai karakteristik COD. Reaktor batch akan digunakan dalam penelitian ini untuk mempertahankan aktivitas mikroba dalam mengubah substrat menjadi bioetanol dalam waktu 72 jam. Nitrogen yang dimurnikan selama 24 jam pertama akan dilakukan untuk menghilangkan sisa oksigen dari reaktor maka gas internal di ruang kepala sistem sirkulasi reaktor akan diganti sebagai sistem pencampuran. Mikroorganisme yang digunakan diambil dari rumen sapi yang dicampur dengan lumpur buangan pabrik kelapa sawit. Studi kinetik akan ditentukan seperti pembentukan produk bioetanol dengan menggunakan model modifikasi Gompertz dan konsumsi substrat menggunakan kinetika orde satu . Nilai Yield dari bioetanol dan asam, serta laju produksi dari bioethanol dan asam juga akan ditentukan. Hasil produksi etanol dari percobaan menunjukkan bahwa kondisi pH optimum dari konsentrasi COD awal 10 g/L berada dalam kondisi netral dan dari 15 dan 20 g/L berada dalam kondisi asam dengan konsentrasi masing-masing 12,36 g/L, 10,42 g/L, dan 20,91 g/L. Menurut karakteristik air limbah POME, konsentrasi COD sekitar 15 g/L kemudian kondisi pH dioperasikan ke dalam kondisi asam (pH 5.5). Dari percobaan limbah cair POME, produksi etanol diperoleh maksimum dalam 72 jam adalah 3,73 g/L. Hasil etanol dan laju produksi POME adalah 1,93 g/g dan 51,87 mg/L /jam. Total hasil asam lemak volatil dan laju produksi dari POME masing-masing adalah 2,34g/g dan 62,95 mg/L/jam. Keywords: pH, kinetik, fermentasi, produksi etanol, limbah pabrik kelapa sawit (POME)